Clinical Utility of Speckle Tracking Echocardiography in Heart Transplantation - Qin Shuxuan, He Qing, Wu Zhenni, Lin Yixia, Ji Mengmeng, Zhang Li, Xie Mingxing, Li Yuman (Advanced Ultrasound in Diagnosis and Therapy, 2025)
Heart transplantation (HT) is a definitive treatment for end-stage heart failure, significantly improving both the quality of life and survival rates of HT recipients (HTx). Speckle tracking echocardiography (STE), a key non-invasive diagnostic method, has become indispensable for providing an in-depth analysis of myocardial mechanics and function. This review focuses on the clinical utility of STE in both pre- and post-transplant settings. The ability of STE to identify subtle cardiac abnormalities and predict post-transplant outcomes underscores its critical role in the clinical management of HTx.